Model Perencanaan Energi Hijau Menggunakan Metode Computable General Equilibrium - Alvina Nur Mala; Rina Mardiati (Departemen Teknik Elektro dan Teknologi Informasi, Fakultas Teknik, Universitas Gadjah Mada, 2018)
Energy is a vital element in our daily life. In line with the demands of energy needs, energy, which is influenced by population and economic growth, has increased continuously. The use of energy is still dominated by fossil energy which is become very limited and the output has not been carried out optimally. In order to realize national’s energy independence and energy sustainability, energy planning is very important for the basic of energy policies management. The objective of this research is to predict the sustainability of new and renewable energy consumption based on National’s Energy policy by the end of 2025 in West Java. This research used the Computational General Equilibrium (CGE) method as an approach to describe the energy balance between supply and demand. The simulation was done using a Green Energy (GREN) scenario by adding several key planning with the projection year in 2016-2025. The results show that the increasing of new and renewable consumption’s percentage in 2025 was 12%. It could be concluded that in 2025, the prediction of the sustainability of new and renewable energy consumption in West Java has reach 23%.